Video in qualitative research : analysing social interaction in everyday life - Heath, Christian, 1952- (SAGE, 2010)
Provides practical guidance for both students and academics on how to use video in qualitative research, how to address the problems and issues that arise in undertaking video-based field studies and how to subject video recordings to detailed scrutiny and analysis.